Advanced Endoscopic Tools - Fung, Eleanor C. (Digestive Disease Interventions, 2021)
The advent and success of therapeutic endoscopy has expanded the utilization of endoscopy as an effective alternative to surgical intervention in some cases with decreased morbidity, improved outcomes, and shortened length of hospital stay. Gastrointestinal bleeding, perforations, leaks, fistulas, and strictures have become increasingly managed by endoscopy with the evolution and development of endoscopic tools for effective closure of full-thickness gastrointestinal defects, dilation, and hemostasis. This article reviews the characteristics and role of endoscopic clips, stents, dilation balloons, endoscopic knives, and suturing devices.
Keywords: clips; stents; tools